Anterior Segment Optical Coherence Tomography in Evaluation of Severe Fungal Keratitis Infections Treated by Corneal Crosslinking. Issue 3 (May 2014) - Abbouda, Alessandro; Estrada, Alfredo Vega; Rodriguez, Alejandra E.; Alió, Jorge L.
Purpose: Anterior segment optical coherence tomography (OCT) is a relevant diagnostic tool in the evaluation of corneal changes following corneal crosslinking (CXL) treatment in patients infected by a severe fungal corneal infection. Methods: Two patients with severe fungal keratitis that was unresponsive to medical treatment were treated with CXL. Corneal melting was present in all cases. Anterior segment OCT showed the preoperative depth and extension of the infiltrate and the modification during the follow-up. Results: Blockage of the melting was achieved in one patient and one patient developed a corneal perforation. Anterior segment OCT allowed control of the evolution of fungal infection and evaluation of the corneal tissue response to the CXL. It is also able to identify the extent and depth of the inflammation. This parameter seems more important than corneal pachymetry to ensure the safety of CXL procedures in infectious keratitis. Conclusions: The different behavior of inflamed tissue with respect to UVA irradiance could be the main point to understand the different postoperative outcome.